2000
DOI: 10.1091/mbc.11.5.1645
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution FRET Microscopy of Cholera Toxin B-Subunit and GPI-anchored Proteins in Cell Plasma Membranes

Abstract: “Lipid rafts” enriched in glycosphingolipids (GSL), GPI-anchored proteins, and cholesterol have been proposed as functional microdomains in cell membranes. However, evidence supporting their existence has been indirect and controversial. In the past year, two studies used fluorescence resonance energy transfer (FRET) microscopy to probe for the presence of lipid rafts; rafts here would be defined as membrane domains containing clustered GPI-anchored proteins at the cell surface. The results of these studies, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
311
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 406 publications
(329 citation statements)
references
References 73 publications
(124 reference statements)
13
311
3
Order By: Relevance
“…S6A). Moreover, staining of the ganglioside GM1 as a marker for lipid rafts (29,30) with the B subunit of cholera toxin revealed a pattern similar to that apparent for the three SFKs in intestinal crypts (see Fig. S6B).…”
Section: Generation Of Iec-specific Csk Cko Micementioning
confidence: 59%
“…S6A). Moreover, staining of the ganglioside GM1 as a marker for lipid rafts (29,30) with the B subunit of cholera toxin revealed a pattern similar to that apparent for the three SFKs in intestinal crypts (see Fig. S6B).…”
Section: Generation Of Iec-specific Csk Cko Micementioning
confidence: 59%
“…Moreover, the results of earlier FRET and electron paramagnetic resonance (EPR)-spin labelling experiments can only be rationalized if rafts are small and unstable, or raft proteins exchange rapidly with non-raft membrane on a timescale of <0.1 ms (REFS 27,28 ). Other FRET studies have shown cholesterol-dependent clustering of certain lipid-anchored proteins on the inner leaflet, but did not estimate domain lifetime or an upper limit of domain size 29 .…”
Section: Lipid Rafts In the Intact Plasma Membrane?mentioning
confidence: 99%
“…Based on FRET criteria, some raft proteins show little evidence for clustering in FRET studies (Kenworthy and Edidin 1998;Kenworthy et al 2000;Glebov and Nichols 2004), Others appear to be clustered in sub-micron domains, as predicted by the lipid raft model (Varma and Mayor 1998;Zacharias et al 2002;Nichols 2003;Sharma et al 2004). Interestingly, detailed analysis of such FRET data has shown that only a small fraction of GPI-anchored proteins are found in clusters and that these clusters consist of only a few molecules (Sharma et al 2004).…”
Section: Methods For Studying Lipid Rafts In Cells and Artificial Memmentioning
confidence: 99%